Sleeve Gastrectomy Associated with Antral Lesion Resection and Roux-en-Y Antrojejunal Reconstruction - Mussa Dib, VR (2023)
Obesity has been growing worldwide, reaching epidemic proportions. Bariatric surgery is the most effective and durable treatment for severe obesity and related diseases. Roux-en-Y Gastric Bypass (RYGB) and Sleeve Gastrectomy (SG) are the most frequently performed bariatric operations, with long-term good results, in terms of weight loss and comorbidities control. Gastroesophageal Reflux Disease (GERD) is commonly associated with obesity. In general, it precludes the indication of sleeve gastrectomy, since this technique has a refluxogenic potential, as shown in many studies. In such cases, RYGB is considered the best surgery, reaching good weight loss and gastroesophageal reflux disease control. The drawback of this technique is that it leaves the remnant stomach, the duodenum, and the proximal part of the jejunum inaccessible. Besides, RYGB makes transoral endoscopic access to the biliary tree impossible. For all these reasons, this bariatric technique is not indicated in cases of gastric polyposis, gastric dysplasia, or strong family history of cancer, among others. We report a case of a morbidly obese patient with intense GERD, for whom a RYGB was precluded due to her strong family history of cancer, even knowing that it would be the best choice for reflux disease control. Instead, SG was chosen, even knowing it could worsen the gastroesophageal reflux disease. The patient signed an informed consent, after being fully enlightened about the risks. During the surgery, a small subserosal whitish lesion was detected, near the pylorus, on the anterior wall of the antrum. Thinking in a Gastrointestinal Stromal Tumor (GIST), it was resected, with a 2 cm safety margin, leaving a 4 to 5 cm hole on the gastric wall. The decision to maintain the proposed sleeve gastrectomy was made, to avoid leaving a remnant stomach, in a patient with such a strong family history of cancer. In the area of the resected lesion, an intraoperative decision was made not to just close the big gastric hole, being afraid of causing some anatomic or functional disturbance in gastric emptying. Instead, we decided to use the gastric opening to construct a Roux-en-Y antrotrojejunal anastomosis, with a 50 cm alimentary limb and a 200 cm biliopancreatic limb. Accordingly, it was performed a sleeve gastrectomy, associated with an antrojejunostomy in a Roux-en-Y fashion. The patient had an uneventful postoperative course. In the second year, she achieved normal weight and good nutritional status, without gastroesophageal reflux symptoms complaints. Seriography study shows that most of the contrast material passes through the antrojejunal anastomosis, instead of the pylorus, while the duodenum is endoscopically patent. This case report shows an unexpected surgical finding that led to a tactic of adding a Roux-en-Y gastric bypass in the antrum, associated with a sleeve gastrectomy, a strategy that may be adopted in cases of morbidly obese patients with important GERD, for whom gastrointestinal exclusions are contraindicated. To confirm this hypothesis, controlled studies are needed.